Pendampingan Penulisan Artikel Publish di Jurnal Terindek Sinta - Djatmiko Hidajat; Dewi Susilowati; Afif Afghohani; Herry Agus Susanto (Jurnal Kemitraan Masyarakat, 2024)
The goal of this community dedication program is to enhance the quality of scientific articles written in SD N.2 Bangsri Purwantoro Wonogiri, with the aim of publishing them in the indexed journal Sinta. The main problems faced were the lack of knowledge of teachers about the quality of scientific articles, the importance of scientific work in IPTEK's growth, and the significance of the author's reputation in indexed journals. The dedication methods used include training, workshops, seminars, and mentoring. Training and workshops are held on a regular basis with the involvement of experts and practitioners of scientific writing. Seminars and discussions feature relevant case studies to enhance the understanding of participants. Program performance evaluation is carried out through periodic monitoring, qualitative and quantitative assessments, as well as results analysis. Program sustainability strategies include sustainable capacity development, mentoring and support, collaboration and networking, and program evaluation and adaptation. The results of this program showed an improvement in the knowledge and skills of teachers in writing scientific articles, as well as an increase in the number of articles submitted and received by Sinta-indexed journals. In conclusion, the program has improved the quality of writing scientific articles in SD N.2 Bangsri Purwantoro Wonogiri and has made a positive contribution to the development of IPTEK in the school environment. Thus, the program is expected to be a model for other schools in improving the quality of scientific articles and publications in indexed journals.